ASPEK HUKUM INTERNASIONAL DALAM PERDAGANGAN SENJATA OLEH NEGARA PEMASOK KE NEGARA MYANMAR YANG DIGUNAKAN DALAM TINDAKAN SERIOUS VIOLATIONS - Rabby, Nur Azizah; Jayakusuma, Zulfikar; Deliana HZ, Evi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Demand supply of weapons the world that continues to increase from year to year to encourage countries advanced to produce weapons suit the needs of the market se to trade weapons into things that are not to be avoided in the business internationally . However , in carrying out arms sales, the supplying country should be pay attention to who the country that will accept if there is record of violations of human rights by weight or not . It is because of the impact that would occur if the case is overlooked quite heavy even countries who often commit acts of crime seriously in law internationally supplied weapons it is not surprising if the weapon is used arbitrarily without regard to the safety of the civilian population or is used as a means of suppressing the community itself . From the background behind the problems mentioned , was born the formulation of the problem , namely , the first What aspects of law internationally against the activities of the trade of weapons that are used in the act of serious violations ? second , How sanctions against the country supplier of arms that are used in acts of serious violations ?. The purpose of writing a thesis is that , to know aspects of law internationally against the activities of the trade of weapons that are used in acts of serious violations and to determine sanctions against the country supplier of arms that are used in the act of serious violations . The type of research that is conducted can be classified study of normative-juridical where research is conducted on the principles of law that dotted the starting of fields governance laws particular , by way of holding the identification of first advance against kaedah-kaedah laws that have been formulated in the legislation of certain . In a study of this source of data used is the data secondary to the material law of primary, secondary , and material legal tertiary are done by way of the study of literature .From the results of research obtained that , first , the action states of participants ATT that supplying weapons to the country Myanmar and used in acts of serious violation against ethnic minorities in Rakhine be reviewed in law treaties international is an action that is contrary to the principle of Pacta Sunt servanda . 2. State member ATT should play a role important to ensure that the use of end guns that they send do not have the risk of bad especially against violations of Rights Rights of Man in accordance with Article 6 of ATT . The existence of a violation of the obligations of international become an indicator for placing the country as the parties who are liable on offense who does . By because it is , accountability countries can be implemented into sanctions for countries participants ATT who violate the agreement are to keep supplying weapons to Myanmar when happened conflicts in countries such . Keywords : Arms Trade Treaty – Serious Violation - and Responsibility State.